2007
DOI: 10.1074/jbc.m701342200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Studies of the HAMP Domain of EnvZ, an Osmosensing Transmembrane Histidine Kinase in Escherichia coli

Abstract: The HAMP domain plays an essential role in signal transduction not only in histidine kinase but also in a number of other signal-transducing receptor proteins. Here Histidine kinases are the major signal transducer in bacteria, playing critical roles in adaptation to external stresses. EnvZ from Escherichia coli is one of the most extensively studied histidine kinases in terms of the functional and structural aspects (1). EnvZ is a transmembrane histidine kinase located in the inner membrane and functions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Evidence for a dynamic conformation being an intrinsic feature of the HAMP domain have already been described in literature (13,14). Moreover, the NMR model was obtained well below the living temperature of the hyperthermophile A. fulgidus, which could have trapped the HAMP structure in one of its most stable conformations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Evidence for a dynamic conformation being an intrinsic feature of the HAMP domain have already been described in literature (13,14). Moreover, the NMR model was obtained well below the living temperature of the hyperthermophile A. fulgidus, which could have trapped the HAMP structure in one of its most stable conformations.…”
Section: Discussionmentioning
confidence: 71%
“…Despite these clear evidences for defined structural elements, indications for an intrinsic fragility of the HAMP domain are obvious. For example, the HAMP domain from NpHtrII was suggested to be in a molten-globule-like state at low salt concentration (13), whereas that from EnvZ, the osmosensing histidine kinase from Escherichia coli, was shown to be unable to form a stable structure by itself (14).…”
mentioning
confidence: 99%
“…1A). CqsS lacks a HAMP domain, which is important in signal transduction in many histidine kinases (32)(33)(34)(35)(36)(37)(38). Thus, interactions between CAI-1 and the final transmembrane domain suggest that this transmembrane domain serves not only in ligand binding but as a critical regulatory region for CqsS kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Protein S can be readily dissociated from myxospores in its soluble form with EDTA. Previously, we also observed that when OmpR, an E. coli transcription factor, is fused to the N-terminal domain (NTD) of protein S, not only does the expression of the OmpR protein improve but also its solubility dramatically increases, by more than 20-fold (9). Importantly, the protein S-OmpR fusion protein exhibits DNA binding almost identical to that of OmpR alone (19).…”
mentioning
confidence: 94%